An experimental study for determination of convective heat transfer coefficients on cooling monofilament - Patkavak, Mert; Demir, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, the convective heat transfer coefficient around small diameter circular wires is determined in an effort to obtain main parameters affecting monofilament cooling process. The different diameter wires and air velocities were employed for detailed research in parallel and cross flow by using a wind tunnel. These correlations were based on conditions used in monofilament yarn production line. The wire diameters which were used in the experiments are vary from 0.2 mm to 1 mm while air velocities 0.5 m/s to 5 m/s as well. These wires were heated with power supply and cooled with specified air flow for the determination of convective heat transfer coefficient. A high precision multi-meter was used to measure the voltage and current values and then the wire surface temperatures have been determined by means of calculated wire resistance. The convective heat transfer coefficients were obtained by subtracting the radiation heat transfer from total heat transfer. The experiments were carried out with different Reynolds numbers. Finally, the resulting Nusselt correlations were compared with the correlations reported by Glicksman, Copley, Fand and Keswani, Churcill and Bernstein, Hilpert, Mc Adams, Dito, Brunig and, Kase and Matsuo. Results are in good agreement with literature for the same range of Reynolds numbers. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Convective heat transfer; Nusselt number; Reynolds number; Wind tunnel; Melt spinning; Quenching; CIRCULAR-CYLINDER; REYNOLDS-NUMBERS; FLOW; EQUATION; LIQUID; AIR; Thermodynamics; Engineering; Mechanics